Who was Neil Armstrong? - Edwards, Roberta (Penguin Group, 2008)
On July 20, 1969, Neil Armstrong stepped on the moon and, to an audience of over 450 million people, proclaimed his step a giant leap for mankind. This Eagle Scout built his own model planes as a little boy and then grew up to be a test pilot for experimental aircraft before becoming an astronaut.
Keywords: Biography & Autobiography; Juvenile Nonfiction